Pemanfaatan Daging Buah Pala Myristica Fragrans Menjadi Manisan Pala Kering - Nurhajarningsi Nurhajarningsi; Abdul Halik; Andi Tenri Fitriyah (PALLANGGA: Journal of Agriculture Science and Research, 2023)
Nutmeg has a fairly high economic value, because apart from being used as a spice, namely the seeds, the flesh of the nutmeg fruit can also be used to make dried candied nutmeg. This study aims to determine the effect of the best concentration of nutmeg pulp and sugar solution on water content, sugar content, vitamin C and the resulting organoleptic tests. The research treatments were nutmeg flesh with concentrations (75%, 70%, 65%, 60%) and granulated sugar with concentrations (25%, 30%, 35%, 40%). Data analysis used a completely randomized design (CRD), with four treatment levels and three replications. Observational data were analyzed using analysis of variance (ANOVA) and follow-up test for BNT. Based on the results of the study, the treatment of adding granulated sugar to dried candied nutmeg had a very significant effect on water content, sugar content, aroma, color and taste, while vitamin C did not have a significant effect. The best results of dried candied nutmeg with the addition of granulated sugar were treatment of 40% sugar solution in terms of water content 14.36%, sugar content 45.22%, vitamin C 651.94 mg, aroma 3.67 (rather like), color 3.72 (like), and taste 4, 20 (likes). Buah pala mempunyai nilai ekonomis yang cukup tinggi, karena selain digunakan sebagai rempah-rempah yaitu bijinya, daging buah pala juga dapat dimanfaatkan menjadi manisan dan produk lainnya. Penelitian ini bertujuan untuk mengetahui pengaruh konsentrasi terbaik antara daging buah pala dan larutan gula terhadap kadar air, kadar gula, vitamin C dan uji organoleptik yang dihasilkan. Perlakuan penelitian yaitu daging buah pala dengan konsentrasi (75%, 70%, 65%, 60%) dan gula pasir dengan konsentrasi (25%, 30%, 35%, 40%). Analisis data menggunakan metode Rancang Acak Lengkap (RAL), dengan empat taraf perlakuan dan tiga kali ulangan. Data hasil pengamatan dianalisis menggunakan analisis keragaman (ANOVA) dan uji lanjutan BNT. Berdasarkan hasil penelitian bahwa perlakuan penambahan gula pasir terhadap manisan pala kering berpengaruh sangat nyata terhadap kadar air, kadar gula, aroma, warna dan cita rasa, sedangkan yang tidak berpengaruh nyata terdapat pada vitamin C. Hasil terbaik dari manisan pala kering dengan penambahan gula pasir adalah perlakuan larutan gula 40% ditinjau dari kadar air 14,36%, kadar gula 45,22%, vitamin C 651,94 mg, aroma 3,67 (agak suka), warna 3,72 (suka), dan cita rasa 4,20 (suka).